Integral atomic layer architectures of 1D crystals inserted into single walled carbon nanotubes - Sloan, J; Kirkland, A; Hutchison, J; Green, M (2002)
The crystal growth behaviour of solid phase halides encapsulated within single walled carbon nanotubes (SWNTs) is reviewed. As SWNTs form atomically thin channels within a restricted diameter range, their internal van der Waals surfaces regulate the growth behaviour of encapsulated materials in a very precise fashion. Crystal growth within SWNTs is therefore atomically regulated and nano-scale crystals with precise integral layer architectures (i.e. 'Feynman Crystals') can be formed. The structural properties of the resulting 1D crystals are principally dictated by the structural chemistry of the bulk material although deviations from bulk crystal growth behaviour are observed. Alternatively, 1D crystals with completely novel structures can form inside SWNTs. Where the encapsulated crystal has a structure recognizably related to that of the bulk material, crystals are formed with lower surface coordination and all exhibit substantial lattice distortions as a result of this reduced coordination and/or van der Waals constriction effects. 1D crystal growth within SWNTs is occasionally impeded by the presence of simultaneously incorporated fullerene molecules.